THE EFFECT OF CAPITAL ADEQUACY RATIO (CAR), COST EFFICIENCY RATIO (CER), AND NET INTEREST MARGIN (NIM) ON PROFITABILITY (Study on Sub-Sector Banking Companies Listed on the Indonesia Stock Exchange for the period 2017-2019) - Pratama, Aldi; Lilia, Wirda (JEBIM Prima, 2022)
Abstract The purpose of this study was to analyze the effect of the variable Capital Adequacy Ratio (CAR), Cost Efficiency Ratio (CER), and Net Interest Margin (NIM) on the profitability of sub-sector banking companies listed on the Indonesia Stock Exchange for the period 2017-2019. This type of research uses quantitative methods. This study uses a sample of companies in the sub-sector banking listed on the Indonesia Stock Exchange. Based on the purposive sampling technique, it was obtained a sample of 27 companies by 43 companies of total population. The data used in this study are secondary data in the form of corporate financial reports obtained from the website www.idx.co.id. The results showed that partially and simultaneously the CAR, CER, and NIM variables had a significant effect on profitability. Keywords: Capital Adequacy Ratio (CAR), Cost Efficiency Ratio (CER), Net Interest Margin (NIM), Profitability.